UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KEMAMPUAN BACA TULIS AL-QUR’AN SISWA SMK YPM 12 TUBAN - Naila Adibatul Husna; Abdul Jalil; Mutiara Sari Dewi (VICRATINA, 2020)
Al-Qur’an is one of the manes of a book reveled to prophet Muhammad, through the angel gabriel wrirren in the mushaf, and narrated gradyally. The problem that exists in the process of learning islam especially the education of the Qur’an ts the lack of interest in reading and writing the Qur’an to student. This research was carried out at SMK YPM Tuban. The method sed in this research in to use a qualitative research and type of case study research. Data collection techniques using the method of observation, interview method, and using the method of dokumentation, and drawing conclusiuns or verification, while the data validity test is with data credibility tests (presistence test), triangulation, and peer discussions. The result of the study found that the efforts of islamic religious education theacher in improfing the literacy ability of Al-Qur’an for grade X students of SMK YPM 12 Tuban by conduction training in reciting (reading and writing Al-Qur’an) oudside the hours of islamic religious education. The activity was directly guided by islamic religious education teachers and brought teacher from outside the special school to guide students in reading and writing the Qur’an.